Individual differences in multilingual speakers’ fluency: a qualitative analysis of speech and eye-movement data - Lehtilä, Elina; Lintunen, Pekka (Walter de Gruyter GmbH, 2026)
The present study aims to examine individual differences in the connections between first (L1), second (L2), and third language (L3) utterance fluency and to investigate the potential of eye-tracking for multilingual cognitive fluency research, extending previous, mainly quantitative, research on the connections between L1 and L2/L3 fluency. Six Finnish multilingual speakers with differing L1 profiles and proficiency levels in the L2/L3 were selected from a larger dataset, and their speech and eye-movement data from picture description tasks in Finnish (L1), English (L2), and Swedish (L1/L3) were analyzed qualitatively, focusing on fluency measures and the relationship between eye movements and fluency features in the three languages. While the results indicated that some fluency measures were connected across all three languages, the results also demonstrated individual variation in the connections between L1, L2, and L3, particularly in the use of stalling mechanisms. The eye-movement data analysis showed that speakers’ eye movements can provide valuable insights into the cognitive processes underlying fluency features during complex, multi-utterance descriptions in different languages. The findings have methodological implications for fluency research, indicating the need for further fluency studies involving multilingual speakers and eye-tracking, and wider implications for fluency teaching and assessment.